Where shall my wond'ring soul begin? the landscape of evangelical piety and thought - Noll, Mark A. 1946-; Thiemann, Ronald F. (Grand Rapids, MI Eerdmans, 2000)
Includes bibliographical references.
Keywords: Evangelicalism